2021
DOI: 10.1371/journal.pone.0247182
|View full text |Cite
|
Sign up to set email alerts
|

Development of an interactive, agent-based local stochastic model of COVID-19 transmission and evaluation of mitigation strategies illustrated for the state of Massachusetts, USA

Abstract: Since its discovery in the Hubei province of China, the global spread of the novel coronavirus SARS-CoV-2 has resulted in millions of COVID-19 cases and hundreds of thousands of deaths. The spread throughout Asia, Europe, and the Americas has presented one of the greatest infectious disease threats in recent history and has tested the capacity of global health infrastructures. Since no effective vaccine is available, isolation techniques to prevent infection such as home quarantine and social distancing while … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…To investigate the COVID-19 epidemic in Ukraine and to assess its dynamics under different mitigation scenarios, we utilized our general stochastic agent-based modeling framework ( Kirpich et al, 2021 ). The model was adjusted to the Ukrainian settings and fit into the observed Ukrainian data.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…To investigate the COVID-19 epidemic in Ukraine and to assess its dynamics under different mitigation scenarios, we utilized our general stochastic agent-based modeling framework ( Kirpich et al, 2021 ). The model was adjusted to the Ukrainian settings and fit into the observed Ukrainian data.…”
Section: Methodsmentioning
confidence: 99%
“…The reported data was separated into three parts. The initially reported cases from March 12, 2020 to April 12, 2020 were retrospectively incorporated into the model as the initial conditions ( Kirpich et al, 2021 ). The reported and model-produced data from April 22, 2020 to July 12, 2020 were used for model calibration, and from July 13, 2020 to August 1, 2020 – for model validation.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Second, our estimated instantaneous reproduction numbers are closely aligned with the daily mobility pattern, suggesting that the lock-down and stay-at-home order are effective for controlling the COVID-19 outbreak in Massachusetts. Previous research also found the NPIs, including lock-down and stay-at-home order, were effective for containing the COVID-19 outbreak and reducing the public healthcare burden in the state of Massachusetts [32], in the United States [33] and worldwide [34,35]. Third, we observed the daily mobility was slowly increasing from May 2020, and this could explain why the reproduction number estimates rose again around May 11, at which point the reopening plan was unveiled for Massachusetts.…”
Section: Plos Computational Biologymentioning
confidence: 93%